Analisis Faktor Penyebab Kurangnya Minat Belajar Siswa Kelas IV SD - Nurjanah, Sri Fitri Nurjanah; Alani, Nabella Alani (Lembaga Bale Literasi, 2025)
The aim of this research is to analyze the factors causing the lack of interest in studying in class IV students at UPTD SDN Wanamekar 3. Interest in learning is an important aspect in education that influences how students participate and achieve maximum learning outcomes. Based on the results of interviews with the homeroom teacher, it was found that the obstacles to students' interest in learning were influenced by external and internal factors. External factors include a less supportive home environment, such as lack of discipline and parental involvement. Meanwhile, internal factors include students' motivation, self-confidence and personal interests. This research uses a descriptive qualitative approach with data collection techniques in the form of observation and interviews. The results of this research show that to increase interest in learning, teachers need to remind students about class agreements, apply appropriate learning strategies, and create an atmosphere that supports the development of student motivation and self-confidence.